THE EFFECT OF INTERNAL AND EXTERNAL FACTORS ON THE FINANCING DISTRIBUTION OF SHARIA BANKS - Indah Rahmawati; Nisful Laila (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to review the effect of internal bank factors and macroeconomics factors such as liquidity, financing risk, profit-loss sharing rate, the level of securities ownership, interest rate, inflation, and economic growth against Islamic bank financing in Indonesia.  The data used for this research is time series data with monthly frequency from January 2014 to December 2019. Autoregressive Distributed Lag (ARDL) Model results show that in the short term, inflation and economic growth have a significant positive effect on Islamic bank financing. While variable liquidity, financing risk, the level of securities ownership and interest rate have negatively correlated with Islamic bank financing. In the long run liquidity, the level of securities ownership, and economic growth is positive and significant, while financing risk and interest rate have a significant negative effect on Islamic bank financing. In otherwise, profit-loss sharing rate is negative and not significant both in the short and long run.  Keywords: ARDL, Financing, Islamic Banking, Internal Bank Factors, External Bank Factors